Paradigma Al-Qur'an tentang Teori-Teori Pendidikan - Komaruddin Sassi (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
There is a tendency of basic footing in the education and teaching process to always refer to the reference to Western paradigms of educational theories that have been built by the characters, which is something natural, such as the theories of empiricism, nativism, and convergence. However, on the other hand, it becomes a dilemma if the tendency is grounded (crystallized) without being balanced with the motivation for Muslim educators to build educational theories from the Qur'anic paradigm. Hasn't it been recognized and believed that the Qur'an in the Islamic worldview is an absolute reference for solving various life problems, and of course that includes building educational theories? This research is a qualitative-exploratory research with a philosophical approach from documents related to the substance of the study, both primary and secondary, then analyzed by "eidetic" and interpretation methods (hermeneutics). The results of this study indicate that the Qur'an as a source of education has principles that serve as a reference for producing educational theories. These principles are monotheism and rabbaniyah, the principles of monotheism and rabbaniyah (divine spirit) are the main basis for building Qur'an-based education. Because it provides an understanding of the Oneness of God as well as the real manifestation of human essence as khalifah fil ardhi (God's representative on earth).